KETIKA IMAN DIUJI DI TENGAH LUKA SOSIAL: PERAN PASTORAL KONSELING BAGI REMAJA YANG TERDAMPAK BULLYING BERDASARKAN PESAN MATIUS 6:25-34 - Thanya Sweety Tan; Agnes E Poli (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2026)
This paper describes the role of pastoral counseling for adolescents experiencing bullying based on the message of Matthew 6:25-34. Bullying is a form of social injury that is increasingly experienced by adolescents and has a serious impact on their psychological and spiritual health. This article aims to examine how the message of Matthew 6:25-34 can be a theological basis for pastoral counseling in accompanying adolescents experiencing bullying, and how the role of pastoral counseling as a strengthening of faith amidst social wounds based on the message of Matthew 6:25-34. This study uses qualitative methods of literature study and historical critical hermeneutics to examine Matthew 6:24-35. The results of the study show that Jesus' message in Matthew 6:25-34 is not to worry about life because God will remain faithful to care for all of His creation and this message also has a pastoral message in accompanying adolescents who experience social wounds due to bullying, namely as a means of assistance in helping adolescents to restore their identity by not worrying and growing a strong faith amidst suffering.